The ends of collage - Etgar, Yuval (Luxembourg & Dayan, 2017)
The title 'The Ends of Collage', refers both literally and metaphorically to the place where collage fulfils its calling - at the ends or edges of pictures and fragments, where separate worlds come together or break apart from one another. But it also suggests an historical paradigm, where collage is considered as a medium that existed in the so called 'age of mechanical reproduction' and has now been overcome by the new logic of the digital age. The book attempts to survey different approaches to- and definitions of collage and the role of this medium in two crucial historical moments: its emergence in the early decades of the 20th century, and the introduction of digital media during the postmodern moment of the late 1970s and early 1980s. Exhibition: Luxembourg & Dayan, New York, USA (27.02 - 06.05.2017) / Luxembourg & Dayan, London, UK (10.03. - 13.05.2017).0
Keywords: Geschichte; Collage; Ausstellungskatalog -- Luxembourg & Dayan -- 27.02.2017-15.04.2017 -- New York, NY; Ausstellungskatalog -- Luxembourg & Dayan -- 09.03.2017-13.05.2017 -- London; Aufsatzsammlung